2011
DOI: 10.1111/j.1601-0825.2010.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of Polygonum Cuspidatum in oral cancer cells through the regulation of specificity protein 1

Abstract: The results from this study strongly suggest that MEPC, its fraction, and Emodin may be potential bioactive materials to cause apoptosis mechanism via the down-regulation of Sp1 in oral cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Several studies found that Sp1 regulates survivin as its downstream target in various cancer cell lines (37,(39)(40)(41). We also found that HESO significantly decreased survivin, suggesting that the downregulation of Sp1 by HESO in HN22 cells resulted in a decrease of survivin expression.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several studies found that Sp1 regulates survivin as its downstream target in various cancer cell lines (37,(39)(40)(41). We also found that HESO significantly decreased survivin, suggesting that the downregulation of Sp1 by HESO in HN22 cells resulted in a decrease of survivin expression.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies reported that Sp1 is overexpressed in many human tumor and cancer cell lines (35,36). Furthermore, we reported that downregulation of Sp1 induces apoptosis in cervical, prostate and oral cancer cells (37)(38)(39). Thus, we examined whether HESO-induced apoptosis was associated with the Sp1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Withania somnifera extract also reduces the overall occurrence of oral tumors by increasing antioxidant activity (21,22). Recently, it has been demonstrated that Polygonum cuspidatum induces apoptotic cell death in oral cancer cells through the regulation of specificity protein 1 (23). This clearly suggests that the extracts of natural products have anticarcinogenic activities against oral cancer.…”
Section: Discussionmentioning
confidence: 93%
“…P. cuspidatum extract contains alkaloids, phenolics, and sterol/terpenes and induces biological activities such as anti-inlammation, antioxidation, and anticancer efects [38]. In A549 and H1650 cells, the ethanol and ethyl acetate extracts of P. cuspidatum can eliminate 1,1-diphenyl-2-hydrazyl (DPPH) and hydroxyl radicals.…”
Section: Reactive Oxygen Species (Ros) and Lung Cancer Therapymentioning
confidence: 99%